The Subtextual Elements of Surprise in Jack Douglas’ Test Rocket - Pasopati, Rommel Utungga; Mohammed, Khaled Ahmed; Hizbullah, Akmal Dafa; Wirnoto, Yasmine Azzah Adillah; Salsabiyla, Raddine; Wijaya, Kusuma (PT. Gudang Pustaka Cendekia, 2024)
This article exposes the matters of elements of surprise in Jack Douglas’ flash fiction entitled Test Rocket. There is a space station sending a test rocket in which any animal may be sent with it. Meanwhile, the rocket comes back but with bigger postures and with a man in it. Through qualitative method and explorative approach, this paper analyses how the mission to other planet in Douglas’ story contains mysteries as well as subtextual surprises. The surprises could be stated as the mouse that is sent and returns as a man, the man is an alien, or the man is the alien waiting for further attacks by his people. The surprise is not clear but implied since audience is asked to think more about how people in the space station think about the test rocket. In conclusion, Test Rocket contains subtextual elements of surprise in which there are unexpected events after sending the mission to Mars. It can also be known that there will always be unbelievable and unexplainable things happening in space.